TECHNICAL MOVEMENT IMPROVEMENT IN WRESTLING THROUGH QUICK STRENGTH DEVELOPMENT: A SCIENTIFIC PERSPECTIVE - Xolikov Oybek Muratovich (Zeta Repository, 2023)
This scientific article explores the benefits of quick strength development for improving technical movement in wrestling. The study was conducted using a sample of wrestlers and analyzed the effects of a specialized training program on their technical abilities. The results showed that quick strength development can significantly enhance technical movement and overall performance in wrestling. The article provides insights into the scientific perspective behind this approach and its potential implications for wrestlers.